A biomechatronic system for the real- time monitoring and modulation of eating behavior: applications in precision health management - Magomedov, Magomed; Khan, Sadaf; Magomedov, Ali; Fatima, Fariya; Mehdi Raza, Ammar; Parvez, Sidrah; Magomedova, Aminat; Fatima, Ghizal (Frontiers in Mechanical Engineering, 2025)
Monitoring eating behaviour is increasingly important in reducing morbidity and mortality from non-communicable diseases one of the risk factors for NCDs, such as cardiovascular diseases is a decrease in the ability to chew as people age. Research shows that increasing the quantity of chews during meals reduces food intake, promotes satiety, and maintains euglycemia. Despite these benefits, a significant portion of the population (64%–80%) does not monitor or pay attention to their chewing habits. This paper presents the development of a biomechatronic food intake monitoring system designed to track the thoroughness of chewing and determine the amount of food consumed. Using artificial intelligence the system can differentiate signals related to eating, such as jaw and head movements, from other movements, such as speaking. The aim of this paper is to review the importance of chewing for maintaining health, examine the relationship between chewing and NCDs, and present a technological solution for monitoring eating behaviour. We will explore the development of a biomechatronic system that helps users monitor their chewing habits, ensuring proper food intake and promoting healthy eating practices.